LTE-Advanced : a practical systems approach to understanding the 3GPP LTE Releases 10 and 11 radio access technologies - Ahmadi, Sassan (Elsevier Science, 2014)
This book is an in-depth, systematic and structured technical reference on 3GPP's LTE-Advanced (Releases 10 and 11), covering theory, technology and implementation, written by an author who has been involved in the inception and development of these technologies for over 20 years. The book not only describes the operation of individual components, but also shows how they fit into the overall system and operate from a systems perspective. Uniquely, this book gives in-depth information on upper protocol layers, implementation and deployment issues, and services.